Print Ready Drawings. Los Angeles, USA, 2024 - Sarah Hearne; Current Interests; Julie Riley; Jenny Leavitt; Christina Huang (ARQ)
We tend to view media reproductions of architectural drawings as straightforward facsimiles of a singular author’s work. In Print Ready Drawings, curator Sarah Hearne dismantles this assumption, turning our attention to the intricate labor and collaboration behind the creation and circulation of architectural images in print media between the 1950s and 1990s. Through reconfigurable installations by Current Interests and commissioned reproductions and films by Julie Riley and Jenny Leavitt, the exhibition foregrounds the collaborative and socio-political dimensions of reprography. By framing architectural drawings as layered, collective artifacts within a material landscape, the project invites us to reconsider established ideas of authorship, revealing unexpected links between architectural practice and the broader fields of graphic production.